Disaster Response Education for the Community in Watugaluh Village, Diwek Sub District, Jombang District - Nafisah, Khudrotun; Syadiyah, Lailatus; Ayu, Nur; Wardhani, Galuh Rachma; Novianti, Finna Nur; Suparto, Suparto; Budiono, Wahyu (Society : Jurnal Pengabdian Masyarakat, 2025)
Indonesia is a country that is vulnerable to disasters. According to the BNPB Disaster Risk Index 2021, most areas in Indonesia are at risk of natural disasters. UNESCO places Indonesia in the seventh position as the country most vulnerable to natural disasters based on geography, geology, climatology, and demography. In Watugaluh Village, Diwek Sub-district, the community faces substantial challenges due to a lack of understanding in dealing with flood disasters. To overcome this problem, our program offers assistance in the form of disaster response socialization by the Disaster Management Agency (BPBD). This research uses a qualitative method. The result of this assistance is a form of education to the community regarding mitigation and rescue when natural disasters such as floods occur, where the community can reduce the risk of flooding. Students of Group F KKM Darul 'Ulum University also made other efforts to overcome the flood problem in Jasem Hamlet, Watugaluh Village by helping to normalize the river and repairing the river embankment bridge. This is done with the aim that the river flow runs smoothly.